Influence of conduction band minimum difference between transparent conductive oxide and absorber on photovoltaic performance of thin-film solar cell. (2nd February 2015) - Murata, Masashi; Chantana, Jakapan; Ashida, Naoki; Hironiwa, Daisuke; Minemoto, Takashi
Abstract: Difference of conduction band minimum ( E C ) between transparent conductive oxide (TCO) and absorber, named Δ E C-TA, in thin-film solar cell is investigated for high cell performance using device simulator. According to the simulation, the optimized Δ E C-TA value is different, depending on the carrier density in buffer layer, N D-B . With Δ E C-TA above 0.6 eV for both N D-B s of 1.0 × 10 13 and 1.0 × 10 18 cm −3, the spike is formed at the TCO/buffer interface, thus decreasing cell performances, especially short-circuit current density owing to impeding photo-generated carriers to TCO. On the other hand, with Δ E C-TA s below −0.2 and −0.4 eV for N D-B s of 1.0 × 10 13 and 1.0 × 10 18 cm −3, the solar cells demonstrate double diode characteristics, thereby decreasing cell efficiency. Eventually, the optimized Δ E C-TA values for high cell performance are proposed to be in the ranges from −0.2 to 0.6 eV and from −0.4 to 0.6 eV for N D-B s of 1.0 × 10 13 and 1.0 × 10 18 cm −3, respectively.